A study of maternal near miss cases at tertiary care centre, Rajkot - Darbar, Aayasha M.; Dudharejia, Kavita; Goswami, Kamal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: A maternal death is one of the most serious complications in obstetrics, with major impact on family members and staff involved. For every woman who dies from pregnancy or childbirth-related causes, it is estimated that twenty more suffer from pregnancy-related illness or experience other severe complications, these are considered as near-miss cases. The aim is to study the prevalence and clinical profile of maternal near miss in a tertiary care centre and assess the underlying socio-demographic variables, complications and contributing factors among near miss cases. Methods: A hospital based prospective observational study was carried out at department of obstetrics and gynaecology at P.D.U medical college and hospital, Rajkot for the period of 18 months. The study population were the patients admitted in the department of obstetrics and gynaecology at P.D.U medical college and hospital, Rajkot. Selection of patients was according to WHO near miss criteria published in 2011. Demographic details, obstetric history along with past medical and surgical history were the main components in patient interview. Results: 12916 live births occurred during the study period. Maternal near miss incidence was 15.79 per 1000 live births; Maternal near miss to mortality ratio was 4.34; Severe maternal outcome ratio was 19.43 per 1000 live births. Anaemia followed by hypertensive disorders in pregnancy were most common disorders seen in our study. Conclusions: In order to decrease maternal mortality, awareness among general public, timely antenatal visits and early detection of complication and timely management is required.